Siting procedure for a nuclear power plant according to the regulations of the U.S. Nuclear Regulatory Commission - Mirek, Paweł (Instal, 2025)
The paper presents the site selection procedure for a nuclear power plant recommended by the U.S. Nuclear Regulatory Commission (U.S. NRC). The practical manner of its mplementation is discussed, using a five-step approach and a three-level structure of siting criteria. A discussion of the factors used to assess the locations under consideration and how to proceed in determining the area of interest with known and unknown nuclear technology is provided. Given the technological and regulatory neutrality of the procedure discussed, its assumptions may prove helpful when conducting a new or revising an existing siting process for a nuclear power facility that is planned for a completely new site.
Keywords: nuclear power plant; siting procedure; site evaluation report